New species and new records of Cosmolaelaps Berlese (Acari: Laelapidae) from the Republic of Korea, with a review of the Korean species of the genus - Oh, Jaeseok; Joharchi, Omid; Lee, Seunghwan; Jung, Chuleui (Zootaxa, 2025)
This paper reports on six species of the genus Cosmolaelaps (Laelapidae) in the Republic of Korea: Cosmolaelaps brevipedestra (Karg) and C. robustochaetes Ma & Lin collected from soil-litter, and Cosmolaelaps cavosternalis sp. nov., C. hallasanensis sp. nov., C. oedipus sp. nov., C. sansungensis sp. nov. collected in association with ants or their nests. The new species are described and illustrated based on morphological characteristics of the adults and immature stages and compared with closely related species. We provide additional morphological information and new illustrations for two other species to facilitate species delimitation. An identification key to all known Korean Cosmolaelaps species is presented, and ambiguities on the identification of C. koreicus Che & Seo are discussed.